2015
DOI: 10.1259/bjr.20140752
|View full text |Cite
|
Sign up to set email alerts
|

223Ra and other bone-targeting radiopharmaceuticals—the translation of radiation biology into clinical practice

Abstract: Ra has been shown to not only have a palliative effect but also a survival prolonging effect in metastatic, castration-resistant prostate cancer with bone metastases. This article reviews the different radionuclide-based approaches for targeting bone metastases, with an emphasis on 223 Ra, and key elements of the underlying radiobiology of these that will impact their clinical effectiveness.Consideration is given to the remaining unknowns of both the basic radiobiological and applied clinical effects of 223 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…The alpha therapy of choice for treatment of metastatic CRPC is 223 Ra dichloride (Xofigo [previously Alpharadin], Bayer HealthCare), which was approved by the U.S. Food and Drug Administration (FDA) on May 15, 2013 [7376]. Because it is a calcium mimetic, 223 Ra dichloride seeks the hydroxyapatite matrix in the bone naturally.…”
Section: Bone Metastases Therapymentioning
confidence: 99%
“…The alpha therapy of choice for treatment of metastatic CRPC is 223 Ra dichloride (Xofigo [previously Alpharadin], Bayer HealthCare), which was approved by the U.S. Food and Drug Administration (FDA) on May 15, 2013 [7376]. Because it is a calcium mimetic, 223 Ra dichloride seeks the hydroxyapatite matrix in the bone naturally.…”
Section: Bone Metastases Therapymentioning
confidence: 99%
“…Advances in knowledge: In this work, two separate points have been investigated: (1) human absorbed dose of INTRODUCTION Nowadays, radiopharmaceuticals have widespread applications in the diagnosis and treatment of various diseases. 1,2 The skeleton is one of the most common sites of metastases in several tumours such as prostate (80%), breast and lung carcinomas (50%). 3 On the other hand, multiple myeloma, as a fatal illness arising from plasma cells in the bone marrow, is an aggressive plasma cell malignancy that can entail an occurrence of progressive pain.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, high linear energy transfer radionucleotides (particularly a-emitters) such as radium-223 have advantages in terms of relative biological effectiveness, enhanced bystander effect, reduced oxygen enhancement ratio and shorter range of radiation emission. This decreases toxicity and delivers higher energy to target tumour cells even in hypoxic sites, with lower probability to target healthy bone marrow cells [104,105]. Radionucleotides act by inducing DNA double strand breaks which when accumulated in target cells lead to cell death.…”
Section: Radium-223 and Other Radiopharmaceuticalsmentioning
confidence: 99%
“…Radionucleotides act by inducing DNA double strand breaks which when accumulated in target cells lead to cell death. Due to unknown mechanisms, bystander cells not directly irradiated may also undergo apoptosis, via the formation of foci of γ-phosphorylated histone protein (γH2A) [104]. Preclinical studies demonstrated radium-223 distribution to osseous sites [106,107] and its effectiveness in decreasing osteolytic lesions in experimental models of bone metastasis [108].…”
Section: Radium-223 and Other Radiopharmaceuticalsmentioning
confidence: 99%